Biophysical evaluation of cells on nanotubular surfaces: the effects of atomic ordering and chemistry - Shokuhfar, Tolou (Dove Medical Press, 2014)
After the implantation of a biomaterial in the body, the first interaction occurs between the cells in contact with the biomaterial surface. Therefore, evaluating the cell–substrate interface is crucial for designing a successful implant. In this study, the interaction of MC3T3 osteoblasts was studied on commercially pure and alloy (Ti6Al4V) Ti surfaces treated with amorphous and crystalline titanium dioxide nanotubes. The results indicated that the presence of nanotubes increased the density of osteoblast cells in comparison to bare surfaces (no nanotubes). More importantly, our finding shows that the chemistry of the substrate affects the cell density rather than the morphology of the cells. A novel approach based on the focused ion beam technique was used to investigate the biophysical cell–substrate interaction. The analysis revealed that portions of the cells migrated inside the crystalline nanotubes. This observation was correlated with the super hydrophilic properties of the crystalline nanotubes.